"Tell it as it is": How Sisom prompts children and parents to discuss their cancer experience. Issue 3 (23rd April 2019) - Tsimicalis, Argerie; Rennick, Janet; Le May, Sylvie; Stinson, Jennifer; Sarkis, Bianca; Séguin, Karine; Siedlikowski, Maia; Choquette, Anne; Louli, Julie
Abstract: Background: Sisom is an interactive computerized tool shown to improve communication between children with cancer and their clinicians in Norway. Concerns that Sisom may prompt disclosure of potentially distressful symptoms during a busy clinical day may deter implementation in practice in other settings. Aim: The purpose of this study was to describe the questions, concerns, and comments that unfolded between children and their parents during the children's use of Sisom within a research context. Methods: A secondary analysis of qualitative interview transcripts derived from the interactions of 39 children with cancer aged 6 to 13 years with Sisom from two previous studies was performed. Thirty‐one of these interactions had at least one parent present during testing. Data were coded and analyzed using content analysis techniques involving an iterative process of data reduction, display, conclusion drawing, and verification. Results: Sisom elicited a verbal response to at least one symptom in the majority of children (n = 33, 85%) and prompted at least one input in 23 of the parents (74%). Sisom prompted children to (1) discuss their thoughts and feelings out loud, (2) categorize their symptoms as pleasant or unpleasant, and (3) reflect on their illness experiences with varying degrees of certainty. Parental input consisted of (1) providing clarification, (2) validating their child's responses, (3) guiding their child's responses, (4) responding on behalf of their child, and (5) making jokes or casual remarks. Conclusion: Sisom prompts children to discuss their thoughts and illness experiences with their parents and to express their emotions. Sisom may be a useful tool to enhance the communication between children with cancer and their parents and clinicians, which may help them express their needs in the health care setting.